Impact of in vitro gastrointestinal digestion on the chemical composition, bioactive properties, and cytotoxicity of Vitis vinifera L. cv. Syrah grape pomace extract - Costa, Joana R. (2019)
Grape pomace (GP) is a major byproduct worldwide, and it is well known for its bioactive compounds, such as fibers and phenolic compounds, that are popular for their impact upon human health, including gastrointestinal health. The objective of this work was to evaluate the chemical composition and biological activities of an enzymatic GP extract, as well as to investigate how gastrointestinal digestion (GID) modulates these properties. GP extract was previously produced using an enzymatic cocktail with xylanase activity and was then exposed to simulated conditions of GID, characterized for its chemical composition, and screened for antimicrobial, prebiotic, and antioxidant activities. The safety of this ingredient after GID was also assessed. GP extract presented high contents of dietary fiber and other carbohydrates, including xylooligosaccharides, in addition to minerals and phenolic compounds. In vitro simulated GID revealed that xylobiose was resistant to gastric conditions, unlike phenolic compounds. The use of 2% (w/v) of this ingredient proved to be a potential carbon source that could be fermented by Lactobacillus and Bifidobacterium spp, even after digestion. The extract also exhibited strong antioxidant and antimicrobial activities against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa; however, after GID, the antioxidant capacity decreased, and the antimicrobial capacity was strongly reduced or lost. Furthermore, the extract safety was also guaranteed on Caco-2 intestinal cells. This novel and green GP extract proved to be composed of relevant bioactive molecules, including xylooligosaccharides, polyphenols, organic acids, and minerals, which provided different biological properties; it has potential applications in the food industry such that it can be used as an ingredient in the development of new functional foods.